Neokamalomyces indicus gen. nov., sp. nov. (Mycosphaerellaceae)—a Septoria-like genus from India - Yadav, Sanjay; Verma, Sanjeet Kumar; Singh, Raghvendra; Singh, Vinay Kumar; Chaurasia, Balmukund; Singh, Paras Nath; Kumar, Shambhu (Phytotaxa, 2022)
A new hyaline coelomycetous fungus discovered on living leaves of Ficus benghalensis (Moraceae) is described and illustrated. Morphologically, it is similar to Septoria or septoria-like genus, but based on cultural characteristics and multigene (LSU-RPB2-ITS) phylogenetic analysis this strain represents an additional lineage in Mycosphaerellaceae. Hence, a new genus and species, Neokamalomyces indicus is proposed.